Recombinant human soluble thrombomodulin as an anticoagulation therapy improves recurrent miscarriage and fetal growth restriction due to placental insufficiency – The leading cause of preeclampsia. (May 2018) - Sano, Takumi; Terai, Yoshito; Daimon, Atsushi; Nunode, Misa; Nagayasu, Yoko; Okamoto, Atsuko; Fujita, Daisuke; Hayashi, Masami; Ohmichi, Masahide
Abstract: Introduction: Placental insufficiency is one of the major risk factors for growth restriction and preeclampsia. The aim of this study is to investigate whether recombinant human Thrombomodulin(r-TM) improves fetal conditions and physiological outcomes. Methods: We used CBA/J × BALB/C mice as a control and CBA/J × DBA/2 mice – a well-studied model of recurrent spontaneous miscarriage. Pregnant mice received daily subcutaneous injections of r-TM or saline from day 0–15. The fetal resorption rate, fetal weight, and litter size were calculated at day 15. Additionally, we analyzed the mRNA expression of angiogenic factors and the concentration of soluble Flt-1 (sFlt-1) using the ELISA kit. Results: The rate of fetal resorption in CBA/J × DBA/2 mice treated with r-TM was significantly lower compared with mice without r-TM treatment. Additionally, fetal weight and litter size were also significantly higher in the r-TM treated mice. Fibrinogen deposition in the labyrinth area of the CBA/J × DBA/2 mice treated with r-TM was significantly lower compared with deposits in the mice untreated with r-TM. As well, r-TM significantly increased the gene expression level of VEGF and Flt-1 mRNA in the placentas of the CBA/J × DBA/2 mice. r-TM treatment also significantly decreased the production of sFlt-1 protein in the placentas of preeclampsia-like diseased mice. Conclusion: r-TM as an anticoagulation therapy has the potential for the medical treatment of recurrent miscarriage and fetal growth restriction due to improved angiogenic factors. Additionally, r-TM treatment has the potential for the recovery of preeclampsia. Highlights: r-TM decreases fibrinogen staining in placentas from CBA/J × DBA/2 mice. r-TM improves fetal resorption and growth restriction in CBA/J × DBA/2 mice. r-TM increases the expression of angiogenic factors in CBA/J × DBA/2 mice. r-TM decreases the concentration of soluble Flt-1 in CBA/J × DBA/2 mice.